2023
DOI: 10.1101/2023.01.13.523698
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The mitochondrial multi-omic response to exercise training across tissues

Abstract: Mitochondria are adaptable organelles with diverse cellular functions critical to whole-body metabolic homeostasis. While chronic endurance exercise training is known to alter mitochondrial activity, these adaptations have not yet been systematically characterized. Here, the Molecular Transducers of Physical Activity Consortium (MoTrPAC) mapped the longitudinal, multi-omic changes in mitochondrial analytes across 19 tissues in male and female rats endurance trained for 1, 2, 4 or 8 weeks. Training elicited sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 116 publications
0
6
0
Order By: Relevance
“…Nilsson and Tarnopolsky (2019) have suggested that in the general population, aerobic exercise training of older adults may partially reverse mitochondrial dysfunction by increasing the mtDNA copy number and mitochondrial volume, transcript and protein expression, and OXPHOS efficiency [ 33 ]. One should note, however, that chronic training is a stressor that results in improvements in mitochondrial volume, structure, and functioning only in organs/tissues experiencing an increased energy demand [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nilsson and Tarnopolsky (2019) have suggested that in the general population, aerobic exercise training of older adults may partially reverse mitochondrial dysfunction by increasing the mtDNA copy number and mitochondrial volume, transcript and protein expression, and OXPHOS efficiency [ 33 ]. One should note, however, that chronic training is a stressor that results in improvements in mitochondrial volume, structure, and functioning only in organs/tissues experiencing an increased energy demand [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Quantification of mitochondrial DNA (mtDNA) was performed and described by Amar, et al . 115 . Briefly, real-time quantitative PCR was performed in duplicate for each of the scWAT samples selected for -omics analysis.…”
Section: Methodsmentioning
confidence: 99%
“…An additional 128 samples were processed with the Universal Plus™ mRNA-Seq with NuQuant library prep protocol from Tecan, which includes globin and ribosomal RNA depletion following the same protocol as Amar et al 59 . These samples were processed in an automated protocol on a Biomek i7 robotic liquid handling system.…”
Section: Rna-sequencing Library Preparation and Sequencingmentioning
confidence: 99%